Analysis of Spatial-Based Correction of Raw Rice Field Land on Potential Land Recommendations in Serdang Bedagai Regency - Mas Pratono; Feby Milanie; Abdi Sugiarto (International Journal of Society and Law, 2024)
Effective regional planning is very important in maintaining food security, especially in areas with significant agricultural potential such as Serdang Bedagai Regency, North Sumatra. This study aims to conduct a spatial-based rice field correction analysis to validate and update rice field data that has been determined through the Decree of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) No. 686 of 2019. Using Geographic Information System (GIS) technology, this study integrates rice field map data, the latest satellite imagery, and field data to evaluate the actual condition of rice fields in Serdang Bedagai Regency. The results of the analysis showed that there was a decrease in the area of rice fields by 704.90 ha compared to the data of the Decree of the Ministry of ATR/BPN, with around 4,645.40 ha of rice fields that have not been mapped. The data obtained also identified potential rice fields based on the availability of irrigation and land conditions, with a total potential land of 41,233.27 ha. Overlay analysis revealed significant differences between raw paddy field data and actual conditions in the field, indicating land conversion that requires special attention. This study provides strategic recommendations for better management of paddy fields and the need to adjust raw paddy land data to support food security. These findings are not only relevant for local policies but can also be used as a model for other regions in Indonesia in their efforts to maintain and manage agricultural land sustainably.